Betathromboglobulin: expression of platelet activation. Coronary thrombosis predictor - Delgado Matallana, Gustavo (2022)
Platelet activity determined by risk factors (RFs) release specific proteins from citosolic granules; betatromboglobuline (B-TG) in one of them which is a marker that indicate platelet adhesion and agreggation and thrombosis risk. In this issue we determine B-TG by inmunologic thecnic of high sensivity (ELISA). We found positive direct relation between RFs incidence and plasmatic B- TG level with significant value p<0,001; in contrast, in the control group B-TG was in normal range.